Identifying relevant concepts and factors for the sustainability of evidence-based practices within acute care contexts: a systematic review and theory analysis of selected sustainability frameworks - Nadalin Penno, Letitia; Davies, Barbara; Graham, Ian D.; Backman, Chantal; MacDonald, Ibo; Bain, Julie; Johnson, Alekhya Mascarenhas; Moore, Julia; Squires, Janet (Université d'Ottawa | University of Ottawa, 2019)
There is growing recognition among healthcare professionals that the sustainability of evidence-based practices (EBPs) within different settings is variable and suboptimal. Understanding why a particular EBP might be sustained in one setting and not another remains unclear. Recent reviews illustrate the need to identify and analyze existing frameworks/models/theories (F/M/Ts) that focus solely on the sustainability of EBPs in specific healthcare settings, such as acute care, to illuminate key determinants and facilitate appropriate selection to guide practice and research.
Keywords: Evidence-based practices/guidelines/programs/interventions; Frameworks; Innovations; Institutionalization; Models; Routinization; Sustainment; Theories; Sustainability; Utilization; Critical Care; Evidence-Based Practice; Humans